TOPOLOGY OF INVESTMENT RESULTS FROM A 100 SHARE PORTFOLIO ON THE INDONESIAN STOCK EXCHANGE PERIOD 2006-2015 - Julia Alfianti; Zulkarnaini; Lakharis Inuzula; Kelvin Andrew (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
In this research, the Fama and French model is used with five independent variables with data from 100 sample shares to explain the influence of these five independent variables on returns. This observation was carried out using quantitative methods for company financial reports which included a sample of 100 shares during the period January 2006 – December 2015. The total number of research samples was 100 (one hundred) companies that consistently had market capitalization values ​​and share prices during the research period. The results of the research show that Market premium (market premium) is significantly positive explaining portfolio excess returns, size (size premium) is significantly positive explaining portfolio excess returns, value (value premium) is significantly positive explaining portfolio excess returns, profitability (profitability premium) is not significantly explaining portfolio excess return, and investment (investment premium) are significantly negative in explaining portfolio excess return. Suggestions for future researchers are to conduct research using more data to obtain a higher level of accuracy, such as increasing the number of companies and extending the research period to more than 10 years. Then you should choose a research period that does not involve certain conditions or phenomena, because in this research period, namely 2006 to 2015, there was a crisis in 2007-2009, which had an impact on investor behavior in considering investing. It is hoped that this will provide better research results.